2012
DOI: 10.1038/srep00644
|View full text |Cite
|
Sign up to set email alerts
|

Identifying States of a Financial Market

Abstract: The understanding of complex systems has become a central issue because such systems exist in a wide range of scientific disciplines. We here focus on financial markets as an example of a complex system. In particular we analyze financial data from the S&P 500 stocks in the 19-year period 1992–2010. We propose a definition of state for a financial market and use it to identify points of drastic change in the correlation structure. These points are mapped to occurrences of financial crises. We find that a wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
229
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 204 publications
(244 citation statements)
references
References 33 publications
4
229
1
Order By: Relevance
“…We find that there is indeed a genuine evolution of the correlation matrix of stocks returns for different markets in the U.S, in Europe and in Japan, a result that confirms recent studies (see e.g. [10,11,12]). We also give a partial description of this temporal evolution.…”
Section: Introductionsupporting
confidence: 90%
“…We find that there is indeed a genuine evolution of the correlation matrix of stocks returns for different markets in the U.S, in Europe and in Japan, a result that confirms recent studies (see e.g. [10,11,12]). We also give a partial description of this temporal evolution.…”
Section: Introductionsupporting
confidence: 90%
“…The largest eigenvalue is known as a spectral radius, representing the principal component of the system. Recently, the largest eigenvalue has been successfully used as a predicting index for sudden changes in complex systems, such as the financial crisis 21,53 and the housing market. 22 Previous studies have suggested that characterizing the largest eigenvalue of an adjacency matrix of complex networks is useful for better understanding the network behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Also models that assume a first-order auto-regressive process have been suggested, see [6]. Our approach to identify different states of a stock market consists in an analysis of a covariance matrix, similar to [22], and of the transaction volumes, like in [24]. The properties of the covariance matrix of asset returns depend on the time horizon T in which they are determined.…”
Section: Introductionmentioning
confidence: 99%